Музично-педагогічні ідеї Василя Верховинця - Панасюк, Світлана (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюється музично-педагогічна діяльність видатного діяча української національної культури, видатного хореографа, музикознавця, етнографа, педагога, диригента і композитора Василя Вікторовича Верховинця. Зазначається, що педагогічна праця була невід’ємною частиною багатогранної діяльності В. Верховинця. Авторка наголошує, що педагогічна спадщина В. Верховинця – значне явище в історії музичної педагогіки. Особливу цінність для музичного виховання дітей має посібник «Весняночка», який склали пісні-ігри, зібрані в народі або створені композиторами та пісенні авторські зразки. Педагогічна та естетична значущість «Весняночки» полягає у тому, що вміщені в ній твори дають дітям змогу відчути на собі благотворну дію музики й слова, танцю і ритмічних рухів. The article considers musical-pedagogical activity of the outstanding figure of the Ukrainian national culture, a prominent choreographer, musicologist, ethnographer, teacher, conductor and composer Vasily Viktorovich Verhovynets. It is noted that the pedagogical work was an integral part of his versatile activity. His pedagogical ideas were crystallized in parallel with the search in the field of folklore, choreography, choral music, acting, and composition. Understanding the great educational power and incomprehensible beauty of folklore, he sought the means of education of students in the love to folk treasures. The author stresses that the pedagogical heritage of V. Verhovynets is a significant phenomenon in the history of musical pedagogy. It consists of training-methodical manuals – "Vesnyanochka" and "Theory of Ukrainian folk dance", "The anthology of the Ukrainian national dances" that reflect Verhovynets’ knowledge and experience, as musician, actor, choral conductor, ethnographer and, finally, the experience of working with children and students of higher educational institutions. These tutorials have a rich teaching material, selected for teaching children to sing and dance, valuable guidance. A special value for the musical education of children has the manual “Vesnyanochka”, which consisted of song-games, collected among the people or created by composers and song samples of authors. The pedagogic and aesthetic significance of " Vesnyanochka" is that the works contained in it give children the opportunity to feel the beneficial effect of music and words, dance and rhythmic movements.
Keywords: Василь Верховинець; музичне виховання; музично-ритмічні ігри; «Весняночка»; національне виховання